Perceraian dan Perkembangan Psikologis Anak: Analisis Tematis Temuan Tinjauan Literatur - Suroso, Untung; Meilan Arsanti (Legitima : Jurnal Hukum Keluarga Islam, 2023)
Purpose – The purpose of this study was to investigate the impact of divorce on children's psychological development, including changes in their behavior, emotional stability, response to stress, and adaptability, and to understand the factors that influence such impacts as social support and parent-child relationships. Methods – This research employing literature review methodology, this study delves into data extracted from pertinent journals, articles, and research studies. The collected data underwent thematic analysis to discern prevalent patterns and themes concerning the ramifications of divorce on children's psychological growth. Key areas of inquiry encompass behavioral shifts, stress levels, and resilience of children in navigating through the aftermath of divorce. Furthermore, this research endeavors to identify factors that may exacerbate or ameliorate these impacts, such as social support and psychological guidance. Findings – The findings of this study underscore that divorce can precipitate psychological effects manifested in alterations in children's behavior, emotional equilibrium, and sense of responsibility. Additionally, children may experience feelings of anxiety, distress, sadness, shame, and bewilderment following divorce. It is anticipated that the insights gained from this study will advance our understanding of the intricate ways in which divorce shapes children's psychological development. Research implications –The findings of this research contribute to theoretical frameworks regarding the psychological impact of divorce on children, shedding light on the nuanced interplay between familial upheaval and children's emotional well-being. This deepened understanding enhances existing theories of child development and family dynamics, offering insights into the mechanisms through which divorce affects children's psychological adjustment and resilience. Originality/value – The findings of this study provide novel insights into the nuanced ways in which divorce shapes children's psychological development. By highlighting the diverse range of psychological effects experienced by children following divorce, this study advances our understanding of the complexities involved in this process, thereby enriching theoretical frameworks in the field of child development and family dynamics.